STUDENTS’ ABILITY IN WRITING CAUSE AND EFFECT SENTENCE AT TWELFTH GRADE OF CULINARY ART, SMKN 2 PARIAMAN - Adzanil Prima Septy; Agnes Mail Nexi (English Language Education and Current Trends (ELECT), 2022)
The purpose of this research was to describe the students’ ability in writing cause and effect sentence at Grade XII of Culinary Art, SMKN 2 Pariaman. The descriptive method was used as the design of this research. The researcher used a total sampling technique and the sample was 29 students. The instrument for collecting the data in this research was a writing test of cause and effect. The result of the analysis showed that the test was reliable. It was supported by the fact that the coefficient correlation was 0.98. It was categorized as having a very high correlation. Then the test was valid in terms of content because it had covered the material that students had learned. Generally, all of the twelfth grade students have been able to write cause and effect sentence. 20.68% of students got good, 55.17% of students got moderate and 36.84% of students got low. In applying grammar 17.24 % of students got good, 44.82% of students got moderate, and  37.93% of students got low. In using vocabulary 17.24 % of students got good, 65.51% of students got moderate, 17.24% of students got low. In mechanics 6.89% of students got very good, 58.62% of students got good, 27.58% of students got moderate, and  6.89% of students got low.   REFERENCES Agustrianti, S. (2014). Improving The Eleventh Grade Students’Ability in Writing Simple Cause Effect Sentences Through Flow Chart. E-Journal of English Language Teaching Society (ELTS).  (2) 1. Retrieved April 15, 2021, from http://jurnal.untad.ac.id/jurnal/index.php/ELTS/article/ view/3018  Andersen, S. (2014). Sentence Types and Structures. California: San José State University Writing Center. Retrieved March 20, 2021, fromhttps://www.sjsu.edu/writingcenter/docs/handouts/    Sentence%20Types%20and%20Functions.pdf Field, M. (2009). Improve Your Written English : Master the essential of grammar, punctuation, and spelling and write wth greater confidence. United Kingdom:  How to Book.  Retrieved March 25, 2021, from https://libgen.is/book/index.php?md5=53AFCD2CAA9D8CD4491322978CB72281 Harmer, Jeremy. (2007). How to Teach English. England: Pearson Education Limited. Indriana, F. S. (2020). An Error Analysis of Using Conjunction in Students’ Writing Cause aand Effect Sentence (A Qualitative Research At The Eleventh Grade Students Of SMA Islam Sudirman Ambarawa In The Academic Year Of 2019/2020). E-repository perpus IAIN Salatiga. Retrieved February 2, 2021, from http://e-repository.perpus.iainsalatiga.ac.id/8469/  Khalel, A., F. (2020). An Analysis of the Third Year Students’ Difficulties to Use Expressions of Quantity in Writing Positive Simple Sentences at the English Department of Bung Hatta University. E-journal Bung Hatta. 5 (2). Retrieved February 15, 2021, from https://ejurnal. bunghatta.ac.id/index.php/JFKIP/article/view/18066 Landon, B. (2013). Building Great Sentences : How to Wrtie The Kinds Of Sentences You Love to Read. New York: The CoursesTM. Retrieved March 22, 2021, from https://libgen.is/book/ index. php?md5=A4084FE55A161955A94104337715BD24 Nainggolan, E, S. (2021). Error Analysis on Simple Present Tense of Students’ Sentences. Universitas Pamulang. Open Journal unpam. Retrieved August 19, 2021, from http://openjournal.unpam.ac.id/index.php/NOSLLTL/article/viewFile/9317/5892  Raimes A. (1983). Techniques in Teaching Writing. New York: Oxford American English. Refnita, L. (2018). Educational research: A guide for beginners. Padang: LPPM Universitas Bung Hatta. Riggs, Ann. (2012). Sentence Types and Punctuation. UK: WFRANKLIN WATTS.